Determinants of interprofessional collaboration in implementing Basic Emergency Obstetric and Neonatal Care (BEmONC) services - Ersianti, Yuninda Loviana; Fernandez, Veronica; Aulia, Rizka; Ladjar, Yohana Filiberta Lumu; Adnani, Qorinah Estiningtyas Sakilah (Majalah Obstetri & Ginekologi, 2025)
HIGHLIGHTS BEmONC has been proven to diminish both newborn and mother death rates and morbidity. The study identified three main areas for improving and assessing the determinants of interprofessional collaboration (IPC) in the implementation of BEmONC services: team performance, management, and BEmONC evaluation.   ABSTRACT Objective: Maternal and infant mortality is a global challenge due to limited healthcare access. The WHO’s BEmONC program in Indonesia aims to reduce MMR and IMR, but its effectiveness is suboptimal due to service-related issues. This study identified factors affecting essential obstetric and neonatal service implementation in primary healthcare facilities. Materials and Methods: A literature review was conducted using a descriptive analysis approach, supported by Mendeley and Biblioshiny in R-Studio. Sixteen peer-reviewed articles were selected from four online databases, based on predefined inclusion criteria. Results: The study identified three critical domains for improving and evaluating the performance of BEmONC teams. These domains include optimizing team efficacy through factors such as healthcare personnel, infrastructure, collaboration, and targeted training. Furthermore, effective BEmONC management is essential, encompassing policy formulation, communication strategies, operational improvements, and robust leadership. Lastly, evaluating the implementation of BEmONC requires consideration of factors such as self-efficacy, healthcare workforce capacity, and societal trust, confidence, and recognition. Key contributors to the success of BEmONC include efficient collaboration, streamlined administration, and focused evaluation. Enhancing maternal and newborn health service delivery can be achieved by addressing infrastructure deficiencies, improving healthcare worker performance, and fostering community trust. Conclusion: Effective teamwork, robust management, and community confidence are pivotal in improving maternal and newborn health outcomes within BEmONC services.